109k views
4 votes
5c squared- d squared+3/2c - 4d...c= -1. d= -4​

User Wouzz
by
4.9k points

1 Answer

4 votes

For this case we have the following expression:


5c ^ 2-d ^ 2 + \frac {3} {2} c-4d

We must find the value of the expression when:


c = -1\\d = -4

Substituting we have:


5 (-1) ^ 2 - (- 4) ^ 2 + \frac {3} {2} (- 1) -4 (-4) =\\5 (1) -16- \frac {3} {2} + 16 =\\5-16- \frac {3} {2} + 16 =\\-11- \frac {3} {2} + 16 =\\- \frac {25} {2} + 16 =\\\frac {-25 + 32} {2} =\\\frac {7} {2}

Finally, the value of the expression is:


\frac {7} {2}

ANswer:


\frac {7} {2}

User Gankoji
by
6.4k points